1996
DOI: 10.1021/jo9522419
|View full text |Cite
|
Sign up to set email alerts
|

Transition Structures for the Aromatic Claisen Rearrangements by the Molecular Orbital Method

Abstract: Ab initio calculations were performed for eight Claisen rearrangements, eqs 1-8. Transition-state (TS) structures of [3,3] sigmatropic rearrangements of reactions 1-4 are similar, but their activation energies (E(a)'s) are different, E(a)(1) < E(a)(2) and E(a)(3) < E(a)(4). From the intermediate of reaction 3, a hydrogen is moved intermolecularly to form the product, o-allyl phenol. The lower reactivities of reactions 2 and 4 relative to reactions 1 and 3 are ascribed to large endothermicities in the sigmatrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
6

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 17 publications
2
25
1
6
Order By: Relevance
“…To study the probability of existence of a radically mechanism for the reaction, the rate constant also had determined in presence of cyclohexene which acts as radical scavenger [24]. The results do not show any considerable changes in the rate of reaction to assign a radical mechanism for the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…To study the probability of existence of a radically mechanism for the reaction, the rate constant also had determined in presence of cyclohexene which acts as radical scavenger [24]. The results do not show any considerable changes in the rate of reaction to assign a radical mechanism for the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the Claisen rearrangement of the unsubstituted parent allyl vinyl ether, MP4/6-31G*//RHF/6-31G* and B3LYP/6-31G* calculations provide activation barriers that correlate well with the experimental values. 28 It was also shown that activation parameters from B3LYP/ 6-31G* calculations for the parent allyl vinyl ether are in better agreement with the experimental data compared to RHF/6-31G* and CASSCF/6-31G*. 29,30 For the Claisen rearrangement of the parent allyl vinyl ether, DFT calculations using the B3LYP functional and the 6-31G*, 6-31G**, and 6-311+G** functional predicted comparable free energies of activation and also provided very good estimates of the transition-state structure judging from the comparison of experimental and calculated kinetic isotope effects.…”
Section: Methodsmentioning
confidence: 99%
“…[24,30] The [3,3]sigmatropic rearrangement of allyl vinyl sulfides [24, 30±33] generally takes place under mild conditions leading to good yields of g-unsaturated thiocarbonyl compounds. The facile nature of the transformation, as compared to the oxygen series, is mainly of kinetic origin [34] and is explained by the cleavage of the CÀS bond being easier relative to the CÀO bond.…”
Section: Introductionmentioning
confidence: 99%